Microfiber loop resonator based temperature sensor - Harun, Sulaiman Wadi; Lim, Kok Sing; Damanhuri, Siti Sarah Ahmad; Ahmad, Harith (European Optical Society, 2011)
A microfiber loop resonator (MLR) is fabricated by coiling a microfiber which is fabricated using a flame heating technique, into itself. A temperature response on a comb spectrum of a fabricated MLR, which is embedded in a low refractive index polymer, is investigated. The spacing of the transmission comb spectrum of the MLR is observed to be unchanged with the temperature. However, the extinction ratio of the spectrum is observed to be linearly decreased with the temperature. The slope of the extinction ratio reduction against temperature was about 0.043dB/°C. The dependence of the extinction ratio on temperature is due to the change in the material's refractive index.